Pengaruh Pengalaman Kerja dan Pengembangan Karir Karyawan Terhadap Kinerja Karyawan di Savero Hotel Depok - Puti Aulia Sukma Sakti; Rahmi Fadilah (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
This research is motivated by the discovery of unfavorable assessments regarding employee performance, as well as self-evaluation methods that have not been maximized, which in turn affect performance outcomes. Additionally, many employees have worked for more than five years but show the potential for declining performance, and the majority of employees have an educational background equivalent to senior high school. The purpose of this study is to analyze the effect of work experience and career development on employee performance at Savero Hotel Depok. This study employs a descriptive quantitative method with a causal associative approach. The total sampling technique was used, involving all 46 employees as the population. Data were collected through questionnaires designed using a five-point Likert scale. Data analysis was conducted using SPSS version 23.00. The results of the hypothesis testing show that work experience has a positive but not significant effect on employee performance, with a significance value of 0.059 (> 0.05). In contrast, career development has a significant positive effect on employee performance, with a significance value of 0.000 (< 0.05). Simultaneously, work experience and career development have a significant effect on employee performance, indicated by an F value of 40.496 and a significance value of 0.000 (< 0.05). The coefficient of determination (Adjusted R Square) is 0.637 or 63.7%, indicating that work experience and career development collectively explain 63.7% of the variance in employee performance, while the remaining 36.3% is influenced by other factors not examined in this study.